BANK PROFITABILITY: THE IMPACT OF THIRD-PARTY FUNDS AND CAPITAL ADEQUACY WITH CREDIT DISTRIBUTION AS A MODERATING VARIABLE - Waode Adriani Hasan; Sri Harwinda; Sariana Sariana (Jurnal Multidisipliner Bharasumba, 2026)
This study aims to analyse the effect of third-party funds and capital adequacy on profitability, with credit distribution as a moderating variable in banking companies. This study uses a sample of financial reports from 35 companies in the banking sub-sector listed on the Indonesia Stock Exchange from 2021 to 2023. The research data was processed using multiple linear regression analysis and Moderate Regression Analysis (MRA). The results showed that the variables of third-party funds and capital adequacy had an effect on profitability, while the variable of credit distribution had no effect on profitability. The MRA test results show that the credit distribution variable cannot moderate the relationship between the third-party funds and capital adequacy variables on profitability.